The Description and Meaninings of Proverbs To-Riolo of Buginese Tribe in South Sulawesi ( A Semantical Analysis ) - Hariratul Jannah; Ratnawati Ratnawati; Sitti Fatimah (Fakultas Sastra - Universitas Muslim Indonesia, 2017)
The is a scientific work which aims to explain about the meaning of proverbs to-riolo buginese tribe. This research is a qualitative research. The data collected by observation, interview and also research library. The scope of the research is in Watampone bone, South Sulawesi.Proverb to-riolo had four basic (1) bravery (2) wealth (3) honesty and (4) intelligence. The findings of this research after collected data and interviewed other about proverb to-riolo the writer can conclude that proverb to-riolo is a culture of buginese. This Proverb was way how to communication to others and apply the good attitude. The research is meant to preserve and provide additional knowledge and insights of classical literature in South Sulawesi